RETRACTED: The efficiency of the working process of a forestry primer with a hydraulic drive of a rotor-thrower - Petkov Alexander; Druchinin Denis; Popikov Petr; Pivtsov Anatoly; Zlenko Andrey; Sharov Andrey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001